Perubahan Nilai Assamaturu pada Masyarakat Bugis Makassar (Studi Kasus Di Dusun Japing Desa Sunggumanai Kab. Gowa) - Ratnah Rahman; Wahyuni Nasruddin (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2022)
Abstract This paper seeks to explain the changes in the value of Assamaturu in the Bugis Makassar community, especially in Sunggumani Village, Gowa Regency. The results of the study explained that kinship relations are quite strong and the value of Assamaturu in the family sphere is still taught, it's just that its application in the middle of society today is not in line with the teaching pattern that has been inherited. Mutual cooperation needs to be maintained and preserved because it has benefits for the life of the community itself, namely being able to strengthen silaturrahim rope relations between relatives, neighbors and the community in general, reunite relations that have been fractured due to conflict and increase the sense of solidarity between fellow hamlet communities. Keywords: Change of Values, Assamaturu', Community, Bugis Makassar